2022
DOI: 10.1155/2022/2906490
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Incidence and Predictors on Mother-to-Child Transmission of HIV among HIV-Exposed Infants in West Guji Zone, Southern Ethiopia

Abstract: Background. The transmission of HIV from mother to child among HIV-positive infants is estimated to be higher than 20%, despite the fact that antiretroviral treatment is available for antenatal mothers with HIV. In Ethiopia, the prevalence of HIV transmission from mother to child among infants aged one and a half years is estimated to be approximately 15.7 percent. Methods. A retrospective cohort analysis using a simple random sampling technique was incorporated among 422 HIV-exposed babies and their mothers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
(33 reference statements)
3
7
0
Order By: Relevance
“…6 The overall incidence of MTCT of HIV among HIV-exposed infants in Ethiopia was 3.44% (95% CI, 2.46-4.81%). The findings of our study are comparable to those of studies conducted in the Amhara Region 24,26,34 West Guji Zone, 35 and Mekelle City. 36 The similarities might be due to similar treatment protocols (WHO Option B plus PMTCT guidelines).…”
Section: Discussionsupporting
confidence: 89%
“…6 The overall incidence of MTCT of HIV among HIV-exposed infants in Ethiopia was 3.44% (95% CI, 2.46-4.81%). The findings of our study are comparable to those of studies conducted in the Amhara Region 24,26,34 West Guji Zone, 35 and Mekelle City. 36 The similarities might be due to similar treatment protocols (WHO Option B plus PMTCT guidelines).…”
Section: Discussionsupporting
confidence: 89%
“…The low proportion of HEI enrolment in HCC at birth highlights a key missed opportunity to begin monitoring HEI. Overall, 60% of HEI had HCC enrolment documentation regardless of the enrolment time by 2 months, consistent with other studies, 47 , 48 lower than the 80% national 2018 and 2022 report. 49 , 50…”
Section: Discussionsupporting
confidence: 89%
“…All 15 eligible studies included in this systematic review and meta-analysis were cross-sectional by study design, reported in English, and performed from 2015 to 2022. The sample size ranged from 41 in the Tigray region [24] to 422 in the Oromia region [23]. Regarding the geographical distribution of the primary studies, six were from Oromia [19][20][21]23,32,33], four were from South Nation Nationalities and Peoples Representatives (SNNPR) [34][35][36][37], two were from Amhara [38,39], two from Tigray [24,40], and one from Harari regional states [41].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Various primary studies regarding the Option B+ program have been conducted in different regions of Ethiopia. These detached studies showed that the level of option B+ program adherence among HIV-positive women in the country ranges from 60% in Oromia [ 23 ] to 95.1% in Tigray [ 24 ]. The report of these detached studies showed that there is a great variation and inconsistency related to adherence to the program among HIV-positive women throughout the country.…”
Section: Introductionmentioning
confidence: 99%